2011
DOI: 10.5251/ajsir.2011.2.6.883.889
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and the preventive strategies of Malaria among Migrant Farmers in Ado-Ekiti Local Government Area of Ekiti State, Nigeria

Abstract: The aim of this study was to investigate the knowledge and the preventive strategies of malaria among migrant farmers in Ado-Ekiti Local Government Area of Ekiti State, Nigeria. The study was a descriptive design of the survey type. The structured questionnaire used for this study was adapted from Matta, Khokhar and Sachdev (2004). The instrument with detailed information on knowledge of malaria disease, the preventive strategies and practice of the preventing strategies was used to elicit information from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 6 publications
3
21
3
Order By: Relevance
“…This high knowledge of malaria prevention concurs with findings from similar studies in south western Nigeria. 11,12 Though three-quarters (75.1%) of the respondents admitted to having bushes around their houses, only 52.4% of them reported that they cleared the bushes weekly. This is a pointer to the need for more intensive public health campaigns on sanitation and hygiene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This high knowledge of malaria prevention concurs with findings from similar studies in south western Nigeria. 11,12 Though three-quarters (75.1%) of the respondents admitted to having bushes around their houses, only 52.4% of them reported that they cleared the bushes weekly. This is a pointer to the need for more intensive public health campaigns on sanitation and hygiene.…”
Section: Discussionmentioning
confidence: 99%
“…This concurs with results from a similar study carried out in Oyo state in 2016 but contrasts with findings from a study that was carried out in 2011 where as much as 59% of the respondents knew about prophylactic malaria drugs and also used them. 4,12 This lack of understanding may not be unconnected to the fact that malaria prophylaxis is generally not recommended for the general population in Nigeria since it is an endemic region. Thus, emphasis must continually be laid on the use of ITN, environmental sanitation while inappropriate use of chemoprophylaxis must be discouraged.…”
mentioning
confidence: 99%
“…Malaria remains one of the major causes of morbidity and mortality in sub-Saharan Africa because the environment favours the multiplication and sustenance of the parasite causing the disease [1]. Malaria is the most serious health problem in tropical and subtropical regions of the world that has emerged one of the top three killers among vector borne disease in the world.…”
Section: Introductionmentioning
confidence: 99%
“…Malaria also hampers children schooling and social development. A study of the knowledge and preventive strategies of malaria among migrant farmers in Ado Ekiti, Ekiti state showed that 92% of the study population have the knowledge about the causes of malaria disease, 86% knew that malaria can be prevented [1]. However, the knowledge as well as preventive strategies of malaria did not translate to improvement in the practice through preventive measures of malaria [5].…”
Section: Introductionmentioning
confidence: 99%
“…[3] A study on the knowledge and the preventive strategies of malaria among migrant farmers showed that 64% of respondents said malaria can lead to death, 85% stated malaria manifests with fever, headaches/body pains and 59% know about and are using prophylactic malaria drugs. [4] Furthermore, the research on knowledge, attitudes and practices about malaria and its control in Tanzania, reported that artemether-lumefantrine was the most common antimalarial therapy used and health facilities were the first option for malaria treatment as said by 47.3% respondents. [5] In Colombia, a study published in 2014 on knowledge, attitudes and practices of malaria, stated that 89.3% respondents said malaria can be cured using tablets.…”
Section: Introductionmentioning
confidence: 99%